Evaluation of Attention-Deficit Hyperactivity Disorder Risk Factors. (10th November 2013) - Golmirzaei, Javad; Namazi, Shole; Amiri, Shahrokh; Zare, Shahram; Rastikerdar, Najme; Hesam, Ali Akbar; Rahami, Zahra; Ghasemian, Fatemeh; Namazi, Seyyed Shojaeddin; Paknahad, Abbas; Mahmudi, Forugh; Mahboobi, Hamidreza; et al.
Abstract : Background . Attention-deficit hyperactivity disorder (ADHD) is one of the most common psychiatric disorders among children. The aim of this study was to evaluate risk factors for ADHD in children. Method . In this case-control study, 404 children between 4 and 11 years old were selected by cluster sampling method from preschool children (208 patients as cases and 196 controls). All the participants were interviewed by a child and adolescent psychiatrist to survey risk factors of ADHD. Results . Among cases, 59.3% of children were boys and 38.4% were girls, which is different to that in control group with 40.7% boys and 61.6% girls. The chi-square showed statistically significance (P value < 0.0001). The other significant factors by chi-square were fathers' somatic or psychiatric disease (P value < 0.0001), history of trauma and accident during pregnancy (P value = 0.039), abortion proceeds (P value < 0.0001), unintended pregnancy (P value < 0.0001), and history of head trauma (P value < 0.0001). Conclusions . Findings of our study suggest that maternal and paternal adverse events were associated with ADHD symptoms, but breast feeding is a protective factor.